PARADIGMA PERENCANAAN PEMBANGUNAN DAERAH DALAM PERSPEKTIF EKONOMI ISLAM - Addiarrahman Addiarrahman (Islam Realitas: Journal of Islamic and Social Studies, 2018)
This article aims to elaborate the paradigm of regional development planning in the perspective of Islamic economics. The need for new perspectives in formulating development planning is quite significant considering the weaknesses and failures of the conventional paradigm which has been the background. The worldview proposed through this paper integrates Islamic values (al-Quran and al-Sunnah) as meta-framework and archetypal models; development goals as contained in the 1945 Constitution and other regulations; local wisdom in each region. Artikel ini bertujuan mengelaborasi paradigma perencanaan pembangunan daerah dalam perspektif ekonomi Islam. Kebutuhan terhadap perspektif baru dalam merumuskan perencanaan pembangunan cukup penting mengingat kelemahan dan kegagalan paradigma konvensional yang selama ini melatarinya. Paradigma yang diusul melalui tulisan ini mengintegrasikan: nilai-nilai Islam (al-Quran dan al-Sunnah) sebagai metaframework dan archetypal model; tujuan pembangunan sebagaimana termuat dalam UUD 1945 dan peraturan lainnya; kearifan lokal yang terdapat di masing-masing daerah.